An Analysis of the Determinants of Non-Performing Financing in Islamic Commercial Banks in Indonesia during the 2015–2024 Period - Utami, Adinda Putri Wulandari; Juniwati, Endang Hatma; Pakpahan, Rosma; Nugraha, Hanafi; Hazma, Hazma (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Non Performing Financing is one of the important indicators in assessing the financial health of Islamic Commercial Banks. This study aims to determine the magnitude of the influence of FDR, BOPO, Net Imbalan, Inflation, and Exchange Rate on Non Performing Financing which is proxied by the NPF ratio. This study uses a quantitative approach with a descriptive method, and the data analysis technique used is panel data regression analysis. The population in this study includes Islamic Commercial Banks in Indonesia registered with the Financial Services Authority (OJK) during the period 2015–2024. The data used is secondary data in the form of a combination of time series and cross-section data, where the bank's quarterly reports are obtained from the official websites of each bank. Data related to inflation and exchange rates are obtained from the official website of Bank Indonesia. The results of this study indicate that FDR and BOPO have a significant positive effect on the NPF ratio. Meanwhile, the Exchange Rate (Kurs) has a significant negative effect on the NPF ratio. Net Imbalan and Inflation do not have a significant effect on the NPF ratio. Simultaneously, all independent variables influence the NPF ratio. The results of this study are expected to provide contributions in the form of useful insights for bank management, especially in managing financing risks. Thus, this study is expected to be able to support the improvement of the stability and performance of Islamic Commercial Banking in Indonesia.